Exploring Professional Help-Seeking for Mental Disorders. (October 2016) - Savage, Hannah; Murray, Joanna; Hatch, Stephani L.; Hotopf, Matthew; Evans-Lacko, Sara; Brown, June S. L.
Only a third of people with mental disorders seek professional help. In this study, we aimed to investigate attitudes toward help-seeking among non-help-seekers drawn from a community survey in South London. We conducted qualitative interviews with 24 participants with symptoms of mental disorders. We analyzed data using thematic analysis. Participants' reasons for not seeking professional help included perceiving their problems as normal or unsuitable for professional help, negative expectations of professional help, believing informal strategies were sufficient, fearing being stigmatized for having a mental disorder and help-seeking, and self-perceptions of being strong and/or self-reliant. A small number ( n = 4) had resolved their problems. Participants with unresolved mental disorders ( n = 20) had more chronic stressors, particularly about finances and family relationships, and greater concerns about professional help and stigma than other participants. Potential targets for interventions to encourage help-seeking could be focused around stigma about help-seeking as well as the self-perception of being strong.